Molecular mousetraps and the serpinopathies. (1st April 2005) - Lomas, D.A.; Belorgey, D.; Mallya, M.; Miranda, E.; Kinghorn, K.J.; Sharp, L.K.; Phillips, R.L.; Page, R.; Robertson, A.S.; Crowther, D.C.
Abstract : Members of the serine proteinase inhibitor or serpin superfamily inhibit their target proteinases by a remarkable conformational transition that involves the enzyme being translocated more than 70 Å (1 Å=10 −10  m) from the upper to the lower pole of the inhibitor. This elegant mechanism is subverted by point mutations to form ordered polymers that are retained within the endoplasmic reticulum of secretory cells. The accumulation of polymers underlies the retention of mutants of α1 -antitrypsin and neuroserpin within hepatocytes and neurons to cause cirrhosis and dementia respectively. The formation of polymers results in the failure to secrete mutants of other members of the serpin superfamily: antithrombin, C1 inhibitor and α1 -antichymotrypsin, to cause a plasma deficiency that results in the clinical syndromes of thrombosis, angio-oedema and emphysema respectively. Understanding the common mechanism underlying the retention and deficiency of mutants of the serpins has allowed us to group these conditions as the serpinopathies. We review in this paper the molecular and structural basis of the serpinopathies and show how this has allowed the development of specific agents to block the polymerization that underlies disease.